2017
DOI: 10.1097/acm.0000000000001617
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Media in Graduate Medical Education: A Systematic Review

Abstract: Purpose Despite the growing presence of social media in graduate medical education (GME), few studies have attempted to characterize their effect on residents and their training. The authors conducted a systematic review of the peer-reviewed literature to understand the effect of social media on resident (1) education, (2) recruitment, and (3) professionalism. Method The authors identified English-language peer-reviewed articles published through November 2015 using Medline, Embase, Cochrane, PubMed, Scopus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
234
1
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(282 citation statements)
references
References 39 publications
(130 reference statements)
5
234
1
19
Order By: Relevance
“…Assessing evidence from other professional disciplines could benefit our understanding of social media in nursing and midwifery education, especially as interprofessional education in healthcare is coming to the fore (Mckay, Steiner, Shekhter, & Birnbach, ; O'Connor, ). Common themes across the reviews from medical and general health education that are in keeping with the findings of this review include evaluating learning outcomes, understanding e‐Professionalism, maximizing flexible learning and online communities for social support, managing workload associated with virtual interactions, and technical difficulties with some social media platforms (Cheston et al., ; Smith & Lambert, ; Sterling et al., ; Whyte & Hennessy, ). These would benefit from further interdisciplinary research to ensure we can learn lessons and implement pedagogical solutions that work for all types of healthcare students.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Assessing evidence from other professional disciplines could benefit our understanding of social media in nursing and midwifery education, especially as interprofessional education in healthcare is coming to the fore (Mckay, Steiner, Shekhter, & Birnbach, ; O'Connor, ). Common themes across the reviews from medical and general health education that are in keeping with the findings of this review include evaluating learning outcomes, understanding e‐Professionalism, maximizing flexible learning and online communities for social support, managing workload associated with virtual interactions, and technical difficulties with some social media platforms (Cheston et al., ; Smith & Lambert, ; Sterling et al., ; Whyte & Hennessy, ). These would benefit from further interdisciplinary research to ensure we can learn lessons and implement pedagogical solutions that work for all types of healthcare students.…”
Section: Discussionmentioning
confidence: 78%
“…Facebook and Twitter were the most commonly used social media applications in the articles reviewed, a finding reported by others, although blogs have been widely used for learning in the health education literature (Cheston et al., ; Sterling et al., ). Social media differs in the range of features and functionality it offers so nurse educators should explore other popular platforms such as Instagram and LinkedIn.…”
Section: Discussionmentioning
confidence: 78%
“…Although there may be real-time peer-review to critique misleading and/or incorrect information, the quality of that content may be variable. Perhaps most importantly, recent research has demonstrated a lack in high-quality evidence, infrequent assessment of skill or behavior-based outcomes, and no assessment of patient-based outcomes 46. What we need is to employ structured processes to better understand the impact(s) social media is having on medical education.…”
Section: Introductionmentioning
confidence: 99%
“…This effect may be modest considering an average improvement of 7 to 8 correct answers in a 50‐question examination. Although Twitter Poll has potential to be an instructional adjuvant in clinical rotations for medical students, other platforms such as Black Board, Survey Monkey, and Qualtrics applications may serve a similar role . The advantage of Twitter Poll is that it provides a short test of knowledge that can be supported using annotated references from the medical literature and links to original articles.…”
Section: Discussionmentioning
confidence: 99%